DEVELOPMENT OF TOUR GUIDE COMPETENCIES IN IMPROVING WORK PROFESSIONALISM AT INDONESIAN TOURISM ASSOCIATION OF CENTRAL JAVA - Hafidzah, Ibna Azka; Hakim, Lukmanul; Susanto, Dedy; Savitri, Fania Mutiara (JURNAL MANAJEMEN DAKWAH, 2024)
This study aims to explore the competency development program of tour guides in improving work professionalism in the Association of Indonesian Guides (HPI) Central Java. The methods used were direct observation, and in-depth interviews with tourists, tour guides, and travel agencies, as well as literature studies. This research identifies factors that influence the improvement of the competence and professionalism of tour guides. The main finding of this research is that a structured, sustainable, systematic tour guide competency development program, full support of stakeholders, and certification recognized by the state can contribute to improving the quality of tour guide services, and tourist satisfaction. This research contributes to the science of da'wah management, seen from how da'wah values can be integrated into the tour guide competency development program to create guides who are not only competent in knowledge, and skills, but also have ethical and moral awareness at work, such as guide coordinating tourists to pray first before traveling, reminding prayer time schedules, and inviting to always do good, especially in terms of preserving the environment by throwing garbage in the place provided.